Don't Miss This! Red Flags in the Pediatric Eye Examination: Ophthalmoplegia in Childhood. Issue 3 (3rd July 2019) - Repka, Michael X.
ABSTRACT: Paralytic strabismus in children is rare, occurring in about 0.1% of children. This rate is far less common than the 3% rate usually noted for comitant strabismus. The relative rates of ocular motor pareses were fourth nerve palsies in 36%, sixth in 33%, third in 22%, with multiple ocular motor nerve palsies in 9%. In a single population series from Minnesota, few cases were associated with neoplasm. However, institutional case series reports a high rate of neoplasm for acquired third nerve and sixth nerve palsies after excluding trauma and congenital causes. Tumor is rare in children with fourth cranial nerve palsies, usually associated with other neurologic disease. Rare causes of external ophthalmoplegia, to be considered when the motility pattern is variable or not fitting an ocular motor nerve pattern, include myasthenia gravis and congenital fibrosis of the extraocular muscles. Myasthenia most often presents as ptosis with exotropia. Rarer still is involvement of the extraocular muscles in childhood thyroid disease.